Is the degree of facial swelling after dental extraction sufficient to justify the current delays to radiotherapy mask production? A pilot evaluation of postextraction swelling using 3D photography. Issue 2 (14th February 2022) - McCormick, Robert; Meechan, John; Adams, James; Stanncliffe, Helen; Merecer, Lee; Best, Kate; Nugent, Michael
Abstract: Background: Concern that facial swelling after dental extractions will spoil the fit of radiotherapy masks in head and neck cancer patients leads to the current practice of delay making of mask production (and therefore the start of radiotherapy) for several days or longer. However, there is little data on how extensive facial swelling is after dental extraction. Aim: To assess the degree of facial swelling in a group of adult patients attending Newcastle Dental School for routine dental extractions. Materials and Methods: Seventeen dental extraction patients underwent three‐dimensional photography using the 3dMDFace® system at 1‐week preop, immediately preop, and at 48‐h postop. We recorded demographic data, teeth extracted, and methods. Facial volume change was assessed using 3dMD Vultus® software. Two reviewers ran the data through the 3dMD Vultus® software independently. We used Student's t ‐test to assess significance. Results: Twelve patients were included in the final analysis. There was no significant difference in the difference between the two preoperative measurements and the preoperative versus postoperative difference (Wilcoxon signed‐rank test: Reviewer 1: p = .31. and Reviewer 2: p = .10). Thus, mean facial swelling was less than the threshold for significant swelling which was deemed to be 15 cm 3 . Conclusion: Facial swelling following dental extraction may not be sufficient in itself to justify the current delays in mask production and subsequent delivery of radiotherapy. Further definitive studies are needed to optimize how dental extractions should be timed within head and neck cancer care pathways.